Magnetic properties of thermal plasma synthesized nanocrystalline nickel ferrite (NiFe2O4) - Nawale, Ashok B.; Kanhe, Nilesh S.; Patil, K. R.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Journal of Alloys and Compounds, 2011)
A rapid synthesis method is reported for magnetic nanoparticles of nickel ferrite involving thermal plasma assisted vapor phase condensation process. The as-synthesized samples were characterized by X-ray Diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and X-ray Photoelectron Spectroscopy techniques. The average particle size was determined from the TEM micrographs and found to be around 30 nm. The effects of reactor parameters on the magnetic and structural properties have been evaluated, to find the optimized parameters so as to achieve the highest values of saturation magnetization and coercivity. Reasonably high saturation magnetization (48 emu/g) has been assigned to the high degree of crystallinity, achieved on account of high temperature during the growth, and the cation redistribution. The high value of coercivity (1150e) is explained on the basis of possible lattice defects arising from the cation redistribution. Detailed analysis of cation distribution using the XRD line intensity data leads to the conclusion that these samples are iron deficit and nickel rich. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic measurements; Magnetization; Nanostructured materials; TEM

Humidity-sensing studies of cerium oxide nanoparticles synthesizedby non-isothermal precipitation - Khadse, V. R.; Thakur, Sharada; Patil, K. R.; Patil, Pradip (Sensors and Actuators B-Chemical, 2014)
We report the fabrication of a highly sensitive and fast humidity sensor based on cerium oxide (CeO2) nanoparticles, which were prepared at low cost via a simple non-isothermal precipitation method. The asprepared CeO2 nanoparticles were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy( TEM) and the results indicated the formation of face centered cubic phase of CeO2 with average crystallite size of approximately 10-12 nm. Humidity sensors based on CeO2 nanoparticles exhibit high and linear response within the whole relative humidity (RH) range of 11-97% at an operating frequency of 60 Hz. The corresponding impedance changes by approximately three orders of magnitude within the entire humidity range from 11% to 97% RH. The response and recovery times are about 2-3 and 9-10 s, respectively, when RH was switched between 11% and 97%. Furthermore, the sensors also show relatively small hysteresis, excellent reproducibility, long term stability and broad range of operation (11-97% RH). The complex impedance spectra of the sensor at different RHs and the equivalent circuit were analyzed to explore the humidity-sensing mechanism. This study demonstrates that the CeO2 nanoparticles prepared by non-precipitation method can be used as the humidity-sensing material for the fabrication of humidity sensors. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: CeO2 nanoparticles; Complex impedance spectra; humidity sensor; Non-isothermal precipitation; TEM